Improving the Social-Emotional Well-Being of a Child With Multiple Developmental Disabilities by Incorporating the Performative Drama Model into the Learning Process - Alenka Vidrih; Tina Grošelj (Center for Educational Policy Studies Journal)
Self-advocacy is an essential skill for effective and successful integration into the wider social environment and is important for psychological and physiological well-being. The Performative Drama Model Ars Vitae was trialled to improve students’ assertiveness and performance in real life. A 12-year-old boy with learning disabilities and multiple developmental disabilities, who had difficulties expressing himself and participating in class, was trained over a three-month period. The model was integrated into his lessons, with a particular focus on developing self-advocacy skills to help him express himself better and assert himself in groups. The activities carried out by the “actor” supported the development of his self-advocacy, classroom integration and communication skills, and improved his academic performance and general well-being.